Calcined low-grade phosphate rock fertilization enhances nitrogen fixation, yield, and grain quality in soybeans - Nakagawa, Andressa; Sarr, Papa Saliou (Frontiers in Plant Science, 2025)
The limited use of chemical fertilizers in developing countries has posed a significant challenge to sustainable crop production. Beyond increasing yields, improving seed nutritional quality is also crucial. This study evaluated the impact of phosphorus (P) fertilization, using calcined low-grade phosphate rock, on soybean growth, yield, and seed quality. Soybean cultivars, Fukuyutaka and Jenguma were grown under three treatments: no P application (–P), triple superphosphate [+P(TSP)], and calcined phosphate rock [+P(PR)]. Both P treatments significantly increased pod number (e.g., 12 pods plant−¹ in (–P) vs. 25 pods plant−¹ in +P(TSP) for Fukuyutaka), seeds number (23 vs. 48 seeds plant−¹), and seed yield (5.03 g vs. 14.51 g plant−¹) compared to the control. However, P fertilization only increased the average individual seed weight in Fukuyutaka. P application also enhanced root nodulation–nodule numbers in Jenguma increased from 22 in (–P) to 102 in +P(PR)–and boosted nitrogen (N) fixation in both cultivars. Shoot dry weight doubled under P fertilization, accompanied significant increases in shoot N and P contents. Seed composition responses varied by cultivar: in Fukuyutaka, P application reduced protein content but increased lipid content, while in Jenguma, P fertilization increased protein content and had little to no effect on lipid content. Overall, the results demonstrate that calcined phosphate rock is an effective and affordable alternative to triple superphosphate for improving soybean growth, nodulation, nitrogen fixation, and seed quality. It offers a promising phosphorus source for smallholder farmers in phosphorus-deficient soils of sub-Saharan Africa.